Perspective toward complementary & Alternative medicines in the prevention of COVID-19 infection - Apurva Agrawal; Ashish Sharma; Medha Mathur; Anita Sharma; Gaurav Modi; Tarang Patel (Wolters Kluwer Medknow Publications, 2023)
Background: Across the globe, people are seeking integrative and holistic measures to prevent coronavirus (COVID-19) infection in the form of complementary and alternative medicines (CAM) with or without conventional medicines. This study was done to know the extent of CAM use for COVID-19 prophylaxis and to know beliefs and attitudes of people related to CAM use in India. Methodology: A pretested and prevalidated questionnaire was circulated on social media. Participants, who completed the online form and gave voluntary consent, were included. The questionnaire included demographic details and questions related to CAM use, preferences with reasons, preparations used, perceived role of CAM in prevention, immunity boosting and side effects, sources of information, etc. Results: Out of 514 responses, 495 were analyzed. 47.07% of respondents were males and 52.93% were females. 66.9% were using CAM for COVID-19 prophylaxis. The association between age, gender, and profession with CAM use was statistically significant (P < 0.05). 41.1% reported CAM use in the past. 36.6% of CAM users were taking "Kadha" and 33% were using ayurvedic medicines. Other frequently used CAM preparations were chyavanprash, giloy, tulsi, ginger, pepper, cloves, honey, sudarshanghanvati, arsenic-30, lemon juice, cinnamon, steam inhalation, ashwagandha, swasarivati, coronil, and warm saline water gargles. 46.9% of the CAM users were on self-medication and 52.3% preferred CAM over allopathy. Conclusion: Complementary and alternative medicine utilization for COVID-19 prophylaxis is widespread and self-medication is prevalent. As no specific cure is available in conventional systems, people believe in traditional medicines more than conventional, yet confusion exists. There is a need of increasing awareness regarding side effects, drug-drug interactions, and self-medication.